Evaluation of Hygienic Treatment of Biowastes by Anaerobic Digestion in Biogas Plants - Poudel, Ram Chandra; Joshi, Dev Raj; Dhakal, Nawa Raj; Karki, Amrit Bahadur (Nepal Journal of Science and Technology, 2010)
Anaerobic digestion in biogas plants is one of the biological methods for safe handling of biowastes. We evaluated the fate of coliforms and pathogens in different biowaste and bioslurry samples. Bacteria were enumerated and identified by culture based microbiological methods and parasites were detected microscopically by formal-ether sedimentation technique. The mean loads of total and faecal coliforms were significantly decreased (P< 0.05) with the anaerobic digestion in the biogas plant. Out of 18 bioslurry samples, only 8 (45%) samples met the USEPA class ‘A' biosolid standard. The mean reduction in load of total and faecal coliforms was observed higher in batch digestion (P< 0.05). The mean load of total and faecal coliforms was significantly (P< 0.05) higher in human and animal excreta. The load of total and faecal coliforms was independent (P> 0.05) of the size of the biogas plant. The result of this study revealed that the degree of sanitizing biowaste depends on digestion type and nature of biowaste. Key words: Anaerobic digestion; Biogas plant; Bioslurry; Biowaste; Coliforms; Pathogens DOI: 10.3126/njst.v10i0.2958 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 183-188